THE RELATIONSHIP BETWEEN TRUST, TURNOVER INTENTIONS AND EMOTIONS: AN APPLICATION - Balkan, M. Onur; Serin, A. Emin; Soran, Semih (European Scientific Journal, ESJ, 2014)
Managerial leaders and directors are required to succeed the method of “sense” and “emotion” very well, to achieve organizational aims (Lee, 2002). Organizations need to manage all the emotions and feelings and concepts that affect persons health and performance (Gross, 1999). Business life dealing with this issue has increased in seriousness because, the effect of emotions in decision making cleared with academic studies. There is a need to find the path to the correct leadership of emotions. Emotions in the organization help to identify thoughts about the presence and desire to work (Jackson, 2006). The main purpose of this study, which should be considered a descriptive survey in the general sense, is to investigate the relationship between emotional expressions, trust and turnover intentions. Two different surveys were used in order to measure and assess the emotions expressions, trust and turnover intentions. The survey conducted on 200 employees of the public sector institution. Data, obtained from questionnaires analyzed through the SPSS statistical packaged software. We found that especially trust factors (Trust in management, co-worker trust and trust to manager) had a significant effect on “satisfaction” factor of turnover intentions. In addition, we found that “Co-worker trust” had a negative and significant effect on “Seek for job” factor of turnover intentions.